Pengaruh Viral Marketing, Online Customer Review, dan Flash Sale Terhadap Minat Beli Pada E-commerce Shopee (Studi Kasus Mahasiswa di Kota Malang) - Putri, Vina Afrilianda; Arifin, Rois; Rahman, Fahrurrozi (UNIVERSITAS ISLAM MALANG, 2024)
Abstract The purpose of this research is to analyze and determine the influence of viral marketing, online customer reviews and flash sales on purchasing interest on Shopee e-commerce. This research uses explanatory research with a quantitative approach. Sampling was carried out on students in Malang City using the Malhotra formula so that the sample in this study was 75 respondents. This research method uses multiple linear regression analysis with SPSS analysis tools. Hypothesis testing uses the t test and F test. The results of this research show that viral marketing, online customer reviews and flash sales have a significant simultaneous effect on buying interest in Shopee e-commerce. The viral marketing and online customer review variables have a partially significant effect on purchasing interest in Shopee e-commerce. Meanwhile, the flash sale variable does not have a partially significant effect on buying interest in Shopee e-commerce. Keywords : Viral Marketing, Online Customer Review, Flash Sale and Purchase Interest